Estigmatização dos adolescentes em conflito com a lei: uma análise a partir do programa televisivo “Balanço Geral”. - Barbosa, Maria Yvelônia dos Santos Araújo (Universidade do Vale do Rio dos Sinos, 2018)
This dissertation presents a study about the stigmatization of adolescents in conflict with the law and the influence that TV has, in order to do so, relating the historical construction of the gaze that one has about the child and the adolescent (which includes the evolution of the laws that dealt with this issue), but that, unfortunately, did not have the same evolution in the eyes of society. Specifically, it is a study of the social representation performed on the adolescent and the young offender who is the target of certain television programs with great influence in the formation of public opinion and on society. In this study, it is possible to clarify a differentiation between "minors" and children, who occupy different denominations according to their social and financial condition, but that in the empirical referent, the TV program researched, ‘Balanço Geral’ transmitted in the Federal District, presented as the denomination given to adolescents involved in situations of committing an infraction. In the proposed analysis, the methodological procedures were developed in stages, the first being the documentary analysis, carried out through a bibliographical survey on the construction of protection of children and adolescents and juvenile stigmatization; on socio-educational measures, legislation dealing with proposals to reduce the age of criminal offenses; and on the effects of the messages brought by the media. The second stage was based on a Content Analysis, seeking the analysis of the phenomenon in a profound way, punctuating its particularities, its relations, as well as its interlocutions in society. It was also used resources of the informational methodologies applied to the qualitative research, more specifically, the software ATLAS.TI. Therefore, based on the investigation of a sample of recorded and transcribed programs, the positioning of the media was evidenced, considering that the facts of violence are due to the fact that adolescents would not be sufficiently responsible and, it would be necessary a more effective action of punishment, which passes through the feeling of impunity, and can be overcome with the reduction of the penal age as a way of solving the problem of violence. It is a fact that these positions do not take into consideration the situations of violence also suffered by the adolescent to whom the infraction is imputed, so that it stands out that the victim had its history interrupted, not knowing a previous story of the offending teenager.
Keywords: Adolescente; Ato Infracional; Violência; Televisão; Estigmatização; Adolescent; Infraction; Violence; Television; Stigmatization; ACCNPQ::Ciências Humanas::Sociologia